Lacuna - Woon, Clarice Shu Hui (2017)
Our animated short film, Lacuna, is a science fiction themed story of two robot pilots, a master and her apprentice, stranded on an alien planet. Throughout their journey, the master has to learn to trust her apprentice’s decisions and actions in order to escape the hostile planet’s wildlife and get to safety. The main theme of the film is about trusting and learning from others, even if they are younger or lower ranked, instead of putting aside their suggestions or not taking them seriously. The film title Lacuna, which is the definition of a missing part, also stands for the space or gap between the relationship of the Master and Apprentice This report is a documentation of my progression of making the final year project film together in a team with 3 other animation students, from the early stages of conceptualization to the film’s final look and outcome. It will also present the new challenges and the learning process encountered while creating the film, such as style development, story conception and the integration of 2D and 3D animation.